2002
DOI: 10.1046/j.1365-8711.2002.05580.x
|View full text |Cite
|
Sign up to set email alerts
|

A parsec-scale study of the 5/15-GHz spectral indices of the compact radio sources in M82

Abstract: Observations of the starburst galaxy, M82, have been made with the VLA in its Aconfiguration at 15 GHz and MERLIN at 5 GHz enabling a spectral analysis of the compact radio structure on a scale of < 0.1 ′′ (1.6 pc). Crucial to these observations was the inclusion of the Pie Town VLBA antenna, which increased the resolution of the VLA observations by a factor of ∼2. A number of the weaker sources are shown to have thermal spectra and are identified as Hii regions with emission measures ∼10 7 cm −6 pc. Some of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
151
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(163 citation statements)
references
References 21 publications
12
151
0
Order By: Relevance
“…Here the northwestern spur seems to be more extended than the northeastern one. McDonald et al (2002) have already mentioned a difference in the distribution of compact radio sources in the core region between the eastern and western part. The western part seems to be more densely populated by supernova remnants than by H  regions; This situation is vice versa in the eastern part.…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Here the northwestern spur seems to be more extended than the northeastern one. McDonald et al (2002) have already mentioned a difference in the distribution of compact radio sources in the core region between the eastern and western part. The western part seems to be more densely populated by supernova remnants than by H  regions; This situation is vice versa in the eastern part.…”
Section: Morphologymentioning
confidence: 99%
“…A large amount of flux in the core region of M 82 has been resolved into ∼100 independent discrete sources, which are a mixture of supernova remnants and ionised regions around newly forming star clusters (Fenech et al 2010;McDonald et al 2002;Wills et al 1997). The prior authors found indications that particles in these dense regions are suffering from free-free absorption processes inside these ionised regions and in the sources itself, which reduces the observed flux for low frequencies.…”
Section: Disentangling the Core And Halo Emissionmentioning
confidence: 99%
“…In the case of M 82, the closest of the three galaxies discussed here, we used the source list in McDonald et al (2002) and Fenech et al (2008), where the authors already discriminate SNe from HII regions based on their spectral shape, brightness temperature, and observed shell structure. In the cases of the more distant galaxies, Arp 299 and Arp 220, we used available spectral information from the literature, and especially, the brightness temperatures inferred from VLBI observations, which for all of the sources correspond to non-thermal radio emitters (e.g., Pérez-Torres et al 2009, for Arp 299A; Parra et al 2007, for Arp 220).…”
Section: Appendix A: Arp 299-a and Arp 220mentioning
confidence: 99%
“…For our analysis, we combined sources catalogued as SNe (or SNR) detected by Wills et al (1997), Allen & Kronberg (1998), McDonald et al (2002), Fenech et al (2008), and Brunthaler et al (2009. These comprise observations at several frequencies with MERLIN, VLA, and VLBA, including a total of 39 sources.…”
mentioning
confidence: 99%
“…With the high angular resolution and high sensitivity of radio interferometric observations, it is possible to detect, resolve and characterise the nature of these compact sources. For example, in M82, approaching 50 compact objects are detected at centimetric wavelengths; the majority of these sources are identified as supernova remnants, the remaining ∼ 1 3 are compact HII regions [6]. Sources like M82 and Arp220 provide an illustrative example of why radio observations are a vital addition to the numerous studies of supernovae at other wavelengths.…”
Section: Introductionmentioning
confidence: 99%